QUEST FOR MEANING OF EXISTENCE OF JAMAL IN DANY BOYLE'S SLUMDOG MILLIONAIRE MOVIE (2008): AN EXISTENTIALIST APPROACH - MARTYASTUTI, ARUMI (2011)
This study is about quest for meaning of existence of Jamal in Slumdog Millionaire (2008) movie. This objective of the study is to apply the existentialist approach to analyze the quest for meaning of Jamal's existence in Slumdog Millionaire. The writer uses Sartre's major point of existentialism to answer the problem of the study. The study is descriptive qualitative research whose the data are taken from script of Slumdog Millionaire. The technique of the collecting data is library research, while the technique of analyzing data is descriptive. Having analyzed this movie, the writer draws the results of the study. First, based on the structural analysis the director successfully delivers the moral message through the excellent unity of structural element. The director wants to say that everyone can show his existence to get equal status, opportunity and freedom to choose their own way to achieve a success. Second, based on the existentialist analysis human have different existence, their existences are based on different being, choice and act. The human's existence is meaningful if he starts his being which has a good action to show his life purpose.